Comparing Urban Qualities: A City Livability Framework Applied to Jakarta and Nusantara Capital City - Pandu K. Utomo; Anisah Azizah; Putri Nopianti; Nur Asriatul Kholifah; Kartika Tristanto; Ratri Bodromulatsih (International Journal of Engineering, Science and Information Technology, 2026)
This research develops a systemic framework for analyzing urban livability by applying the DPSIR (Drivers, Pressures, States, Impacts, Responses) model to the contrasting cases of Jakarta, Indonesia's established megacity, and Nusantara Capital City (IKN), the planned new capital. Through a systematic literature review and comparative case analysis, we move beyond static indicators to reveal the dynamic causal mechanisms shaping livability. The findings indicate that Jakarta's unmanaged organic growth has established a negative feedback loop of uncontrolled urban intensity, resulting in three interrelated consequences: significant environmental deterioration, substantial economic losses from persistent congestion, and compromised resident well-being. In contrast, IKN's "Forest City" plan represents a comprehensive attempt to integrate density, Diversity, access, and Form from the outset. However, this planned approach is risky. If neighbourhoods lack lively shops and services, people may not use the excellent public transit. Also, if new development makes housing too expensive, it could push out the very people the city is meant to serve. The DPSIR framework proves invaluable for diagnosing these complex interdependencies, offering a practical tool for anticipatory governance. The comparative analysis underscores that creating livable cities requires managing entire causal pathways through integrated, adaptive policies rather than pursuing isolated interventions. This research provides critical insights for Indonesian urban policy and contributes a robust analytical approach to the global pursuit of cities that balance development with human dignity and resilience.